"Pre-icfes digital tool” to improve english competencies on the saber 11 test for the english module: lessons from the Guimarc school (2023)
This research proposes the design, implementation, and assesment of a digital educational resource using the flexible B-learning methodology. The material combines virtual learning, counseling, and face-to-face classes guided by a teacher or tutor. This material is aimed at strengthening the competencies evaluated in the English module of the SABER11 test. It also seeks to familiarize students with the different types of questions as well as to provide useful guidelines for taking the test.